The effects of the time of intranasal splinting on bacterial colonization, postoperative complications, and patient discomfort after septoplasty operations - Karatas,Abdullah (2016)
Abstract Introduction: The main reason for nasal tampon placement after septoplasty is to prevent postoperative hemorrhage, while the secondary purpose is internal stabilization after operations involving the cartilaginous-bony skeleton of the nose. Silicone intranasal splints are as successful as other materials in controlling postoperative hemorrhages of septal origin. The possibility of leaving the splints intranasally for extended periods helps stabilize the septum in the midline. However, there is nothing in the literature about how long these splints can be retained inside the nasal cavity without increasing the risk of infection, postoperative complications, and patient discomfort. Objective: The current study aimed to evaluate the association between the duration of intranasal splinting and bacterial colonization, postoperative complications, and patient discomfort. Methods: Patients who had undergone septoplasty were divided into three groups according to the day of removal of the silicone splints. The splints were removed on the fifth, seventh, and tenth postoperative days. The removed splints were microbiologically cultured. Early and late complications were assessed, including local and systemic infections, tissue necrosis, granuloma formation, mucosal crusting, synechia, and septal perforation. Postoperative patient discomfort was evaluated by scoring the levels of pain and nasal obstruction. Results: No significant difference was found in the rate of bacterial colonization among the different groups. Decreased mucosal crusting and synechia were detected with longer usage intervals of intranasal silicone splints. Postoperative pain and nasal obstruction were also diminished by the third postoperative day. Conclusions: Silicone splints were well tolerated by the patients and any negative effects on postoperative patient comfort were limited. In fact, prolonged splint usage intervals reduced late complications. Long-term silicone nasal splint usage is a reliable, effective, and comfortable method in patients with excessive mucosal damage and in whom long-term stabilization of the bony and cartilaginous septum is essential.